Postpartum care for hypertension prevention in women with a history of preeclampsia: A systematic review - Kusumaningrum, Tiyas; Nursalam; Triharini, Mira; Soares, Domingos (Universitas Airlangga, 2025)
Introduction: Preeclampsia is a risk factor for maternal hypertension, including postpartum hypertension. However, postpartum hypertension is often missed, due to the suboptimal quality of postpartum care and the lack of follow-up in women with a history of preeclampsia. Objective: This systematic review aims to synthesize and evaluate existing interventions for preventing postpartum hypertension in women with a history of preeclampsia, using a narrative synthesis approach to assess their effectiveness and methodological quality. Methods: This systematic review used articles from Scopus, CINAHL, and PubMed. The search focus was postpartum care for hypertension prevention, particularly in women with a history of preeclampsia. Articles published between 2019 and 2024 were selected based on predefined eligibility criteria. We selected fully accessible articles that focused on postpartum care. The keywords used in the article search were “history of preeclampsia” OR “hypertensive disorder during pregnancy“ AND “postpartum” AND “hypertension.” The selected articles came from various countries in five continents (Asia, Africa, Europe, America, Australia, and Europe). The selection process adhered to the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. Results: There were 28 articles reviewed. Postpartum care involving education and regular follow-up increased knowledge and ability to control hypertension risk in women with a history of preeclampsia. There were six articles involving participants performing blood measurements independently and reporting them through an online application or in a text based format. Conclusion: This review confirms that women with a history of preeclampsia, especially severe preeclampsia, are at higher risk of postpartum hypertension. Tailored postpartum care is needed to mitigate the risk of postpartum hypertension and reduce rehospitalization. Continuous follow-up by health workers, either through face-to-face or telehealth monitoring, is important to ensure that mothers receive information and support in managing hypertension risk. Keywords: hypertension; postpartum care; preeclampsia; prevention; telehealth